2021
DOI: 10.3390/ma14143913
|View full text |Cite
|
Sign up to set email alerts
|

The Role of La2O3 in Enhancement the Radiation Shielding Efficiency of the Tellurite Glasses: Monte-Carlo Simulation and Theoretical Study

Abstract: The radiation shielding competence was examined for a binary glass system xLa2O3 + (1 − x) TeO2 where x = 5, 7, 10, 15, and 20 mol% using MCNP-5 code. The linear attenuation coefficients (LACs) of the glasses were evaluated, and it was found that LT20 glass has the greatest LAC, while LT5 had the least LAC. The transmission factor (TF) of the glasses was evaluated against thicknesses at various selected energies and was observed to greatly decrease with increasing thickness; for example, at 1.332 MeV, the TF o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Since these tellurite glasses are heavy and classified as heavy metal oxide, these have found applications as radiation shielding materials replacing toxic lead-based compounds [26][27][28][29]. Computational studies on binary lanthanum-tellurite glasses had shown a higher increase in linear and mass attenuation coefficients, indicating the importance on La 2 O 3 in shielding high energy radiation [30]. This is owing to increase in density and molecular weight of glasses with La 2 O 3 doping.…”
Section: Introductionmentioning
confidence: 99%
“…Since these tellurite glasses are heavy and classified as heavy metal oxide, these have found applications as radiation shielding materials replacing toxic lead-based compounds [26][27][28][29]. Computational studies on binary lanthanum-tellurite glasses had shown a higher increase in linear and mass attenuation coefficients, indicating the importance on La 2 O 3 in shielding high energy radiation [30]. This is owing to increase in density and molecular weight of glasses with La 2 O 3 doping.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the extraordinary qualities that TeO 2 glasses possess. Recent studies have demonstrated that TeO 2 glasses have significant shielding capabilities that are either on par with or even better than those afforded by other kinds of glass systems (Almuqrin et al, 2021). The ability to employ telluritebased glasses in a radiation-contaminated environment depends critically on understanding their shielding efficacy and ability to reduce radiation exposure severity (Çelikbilek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%